PENGARUH CITA RASA, PROMOSI MEDIA SOSIAL DAN HARGA TERHADAP LOYALITAS PELANGGAN CAFE GREEN HOUSE DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING - Nilawati, Dian Wahyu; Karnadi, Karnadi; Fandiyanto, Randika (Fakultas Ekonomi dan Bisnis, 2024)
The aim of this research is to analyze the influenceTaste, Social Media Promotion and Price on Customer Loyalty at Green House Cafe with Customer Loyalty as an Intervening Variable. By using the Partial Least Square (PLS) Structural equation model. Results of direct influence hypothesis testing using the Smart PLS 3.0 application.Taste has a significant positive effect on customer satisfaction Social media promotion has a positive but not significant effect on customer satisfaction Price has a significant positive effect on customer satisfaction Taste has a positive but not significant effect on customer loyalty Social media promotion has a significant positive effect on customer loyalty Price has a positive but not significant effect on customer loyalty Customer satisfaction has a significant positive effect on customer loyalty Taste has a positive but not significant effect on customer loyalty through customer satisfaction Social media promotion has a positive but not significant effect on customer loyalty through customer satisfaction AndPrice has a positive but not significant effect on customer loyalty through customer satisfaction